Design and Construction of an RFID and IoT-Based Attendance System to Improve the Efficiency of Employee Attendance Management at the Indonesian Polytechnic of Piksi Ganesha - Dimas Aditia Firmansyah; Jati Sumarah; Asni Tafrikhatin; Ajeng Tiara Wulandari; Rizdam Firly Muzakki (Jurnal E-Komtek, 2026)
Attendance systems that still rely on manual input require more processing time due to the absence of an automatic identification mechanism, resulting in less efficient attendance recording. This study aims to design and develop an employee attendance system based on Radio Frequency Identification (RFID) and the Internet of Things (IoT) integrated with a web-based application. The research employed the Research and Development (R&D) method using the ADDIE development model. The system was developed using an ESP32 microcontroller, an RFID RC522 Reader, PHP, and MySQL, while IoT technology was utilized to transmit attendance data to the server via the internet. The test results indicate that all system functions operated successfully, including RFID card identification, data transmission, database storage, and attendance information display on the website. Furthermore, the developed system improved attendance processing efficiency by reducing the attendance time from 15–20 seconds to 2–5 seconds. Therefore, the proposed RFID and IoT-based attendance system can serve as an effective and efficient alternative for managing employee attendance.